Asia/Pasific area traffic forecasts 2004-2020 - International Civil Aviation Organization (Canada : International Civil Aviation Organization, 2005)
This report includes medium-term forecasts of air traffic in the transpacific area, in the Asia/Pacific region, and for selected Transpacific and Asia /Pasific city-pair markets through to 2007. The reports also contains a long-term forecast with a horizon to the year 2020, including intermediate forecasts for each of the years 2005-2010, 2010-2015 and 2015-2020.
System requirements: Adobe Acrobat Reader.
Keywords: Aeronautics, Commercial -- Passenger traffic -- Statistics